2015
DOI: 10.1007/s00259-015-3008-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between myocardial perfusion abnormalities and poststress left ventricular functional impairment on cadmium-zinc-telluride imaging

Abstract: Stress-induced LV diastolic impairment is associated with a less extensive ischaemic burden and CAD extent than poststress systolic dysfunction, which is limited to patients with multivessel CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…9,10 Accordingly, recent reports have consistently demonstrated that the integrated evaluation of myocardial perfusion and LV systolic and diastolic functional measures may further increase the accuracy of SPECT imaging in detecting CAD, possibly allowing a more accurate risk stratification of patients with suspected or known disease. 11,12 However, despite these obvious clinical advantages, MPS is characterized by two major technical drawbacks, such as the cumulative radiation exposure 13 and the lengthiness of the imaging protocol, 14 that classically limit its diffusion and make the clinician frequently favor other non-invasive imaging modalities.…”
Section: 5mentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 Accordingly, recent reports have consistently demonstrated that the integrated evaluation of myocardial perfusion and LV systolic and diastolic functional measures may further increase the accuracy of SPECT imaging in detecting CAD, possibly allowing a more accurate risk stratification of patients with suspected or known disease. 11,12 However, despite these obvious clinical advantages, MPS is characterized by two major technical drawbacks, such as the cumulative radiation exposure 13 and the lengthiness of the imaging protocol, 14 that classically limit its diffusion and make the clinician frequently favor other non-invasive imaging modalities.…”
Section: 5mentioning
confidence: 99%
“…21,23 Nevertheless, as previously mentioned, early MPS imaging might offer the chance to perform not only a better evaluation of severity and extension of perfusion abnormalities, but a more physiological assessment of LV functional status under stress conditions. 7,11 In fact, it has been classically shown that myocardial ischemia results in reversible alterations of LV diastolic, at first, and contractile functions, subsequently.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 In this regard, the results of Do et al demonstrate that the concept of ''fast imaging'' can be applied also to dynamic CZT acquisitions, further increasing patient's comfort. Considering that a significant reduction of the waiting intervals between acquisitions can be similarly accomplished without losing diagnostic accuracy, 20 it might be envisioned that in the near future ultrafast CZT imaging also including dynamic acquisitions will replace conventional MPI, allowing increased diagnostic accuracy and improving patient's comfort.…”
mentioning
confidence: 99%
“…1,7 Moreover, SPECT MPI study can provide information on LV structure and function that may both contribute to the diagnostic process, and provide independent measures of adverse patients prognosis. 8,9 Nevertheless, even with the evident advantages of nuclear cardiac imaging, SPECT MPI is also characterized by some relevant drawbacks that should be always taken into account, particularly if traditional Anger cameras are employed. Above all, the relatively high radiation burden of a stress/rest imaging protocol performed with a classical SPECT camera equipped with Na/I scintillating crystals-especially if 201 Tl was used as radiotracer instead of the more favorable 99m Tcbased compounds-has always represented a theoretical limitation of this imaging modality, 10 making the clinician often favor other non-ionizing non-invasive myocardial imaging techniques.…”
mentioning
confidence: 99%